Coupling between infraslow activities and high‐frequency oscillations precedes seizure onset. Issue 3 (8th August 2020) - Hashimoto, Hiroaki; Khoo, Hui Ming; Yanagisawa, Takufumi; Tani, Naoki; Oshino, Satoru; Kishima, Haruhiko; Hirata, Masayuki
Abstract: Infraslow activities and high‐frequency oscillations (HFOs) are observed in seizure‐onset zones. However, the relation between them remains unclear. In this study, we investigated phase‐amplitude coupling between infraslow phase (0.016‐1 Hz) and HFOs' amplitude of focal impaired awareness seizures followed by focal to bilateral tonic‐clonic seizures, in a 28‐year‐old right‐handed man with a dysembryoplastic neuroepithelial tumor. We recorded five habitual seizures. After the time of seizure onset, a significant increase in the power of HFOs was observed, and the power was significantly coupled with θ (4‐8 Hz) phase. In contrast, coupling of infraslow activities and HFOs surged a few minutes before the seizure‐onset time, and ictal HFOs discharged after that. Collectively, our results show that coupling of infraslow activities and HFOs precedes the seizure‐onset time. We infer that such coupling may be a potential biomarker for seizure prediction.